Analisis Rencana Anggaran Biaya Operasional Sebagai Alat Perencanaan dan Pengendalian Pada PT. Trigada Laroiba Mitra - Wahjuny Djamaac; Rizal Bakti; Agustini Agustini; Rio Rio; Rizka Erdianti Saputri (CV. Ulil Albab Corp, 2024)
The purpose of this study is to find out whether the Survey Operational Budget Plan has become a tool of control and control at PT. Trigada Laroiba Mitra in 2021. This research is sourced from data on the Budget Plan financial statements which were analyzed using qualitative descriptive methods aimed at analysis. and summarize the condition of various observations regarding problems that occur in the field. The sample used is a sample of 16 toll road sections at PT. Trigada Laroiba Mitra in 2021. The results of this study indicate that in 2021 the operational costs of a survey of 16 toll road sections at PT. Trigada Laroiba Mitra show that it is not profitable because the realization is greater than budget. Survey operational costs in 2021. The realization after controlling is Rp. 159,385,380, - While the budget that has been determined by PT.Trigada Laroiba Mitra is Rp. 136,350,000, - There is a difference of Rp. 23,035,380,- at the time of control, the PT.Trigada Laroiba Mitra project in 2021 there will be negative deviations or called Unfavorable.